2007
DOI: 10.1111/j.1751-9004.2007.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Similarities and Differences between Women and Men across Cultures

Abstract: Most research looking at psychological similarities and differences between women and men has been carried out in North America and Western Europe. In this paper, I review a body of cross-cultural evidence showing that it is precisely in these Western countries that women and men differ the most in terms of personality, self-construal, values, or emotions. Much less-pronounced gender differences are observed, if at all, in Asian and African countries. These findings are unexpected from the perspectives of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 63 publications
(118 reference statements)
1
39
0
Order By: Relevance
“…Future research should examine multiple control variables in ways that allow for a more complete evaluation of these alternative explanations (see Nettle 2009). Guimond et al (2007Guimond et al ( , 2008 have suggested that sex differences in self-reported personality traits are suppressed in less progressive nations because of reference-group effects. That is, men and women may compare themselves only to their own gender when completing surveys in less progressive cultures, but in more progressive nations men and women compare themselves to everyone, resulting in more accurate sex differences in nations with egalitarian sex role socialization and greater sociopolitical gender equity (Biernat et al 1991).…”
Section: Nation-level Covariates As Alternative Explanationsmentioning
confidence: 98%
“…Future research should examine multiple control variables in ways that allow for a more complete evaluation of these alternative explanations (see Nettle 2009). Guimond et al (2007Guimond et al ( , 2008 have suggested that sex differences in self-reported personality traits are suppressed in less progressive nations because of reference-group effects. That is, men and women may compare themselves only to their own gender when completing surveys in less progressive cultures, but in more progressive nations men and women compare themselves to everyone, resulting in more accurate sex differences in nations with egalitarian sex role socialization and greater sociopolitical gender equity (Biernat et al 1991).…”
Section: Nation-level Covariates As Alternative Explanationsmentioning
confidence: 98%
“…A number of recent studies have examined cross-cultural patterns of sex differences in traits such as self-reported personality, emotions, and values, and these studies have often yielded the unexpected result that sex differences tend to be larger in gender egalitarian, economically developed nations than in gender non-egalitarian, less developed nations (Guimond, 2007). Several theories have been offered to explain these counter-intuitive findings.…”
Section: Introductionmentioning
confidence: 97%
“…That is, the help-self appeal is adapted to men, who have a justice-orientation, and the help-others appeal is adapted to women, who have a care-orientation (cf. Gilligan, 1982;Guimond, 2008;Lyons et al, 2005).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A basic tenet in the field of persuasion is to adapt messages to receiver characteristics, such as level of sensation-seeking (Stephenson andSouthwell, 2006), self-construal (Van Baaren andRuivenkamp, 2007), or cultural values (Aaker and Schmitt, 2001). Given the abundant research evidence for gender differences in the preference for values relating to help-others appeals and to help-self appeals (e. g., Cross and Madson, 1997;Ford and Lowery, 1986;Gilligan, 1982;Guimond, 2008;Lyons, Duxbury, and Higgins, 2005), readers' gender appears to be an appropriate basis for adaptation. Men typically take on an instrumental, agentic role, which can be characterized as being self-focussed and task-oriented, and as emphasizing instrumental self-protection, self-assertion, isolation, and repression of emotion (Lyons et al, 2005).…”
Section: Help-others and Help-self Appeals Adapted To Gendered Valuesmentioning
confidence: 99%
See 1 more Smart Citation